An access control protocol for IoT‐based critical infrastructure in smart grid environment. (13th February 2022) - Badar, Hafiz Muhammad Sanaullah; Obaidat, Mohammad S.; Mahmood, Khalid; Saher, Najia; Ayub, Muhammad Faizan; Khan, Dost Muhammad
Summary: Information and communication technology (ICT) can add appealing attributes such as transparency, energy conservation, cost reduction, reliability, and efficiency to the traditional power grid. The addition of these attributes is possible due to the concept of a smart grid (SG). However, ICT applications engender new access control challenges. Therefore, many studies have been conducted in recent years to investigate that the most significant challenge of the smart grid is privacy. In the light of these studies, two significant problems have been identified for SG access control protocols that must be addressed. First, we have all essential security requirements such as integrity, confidentiality, and authentication. Moreover, the cryptographic algorithms impose significant computational and communication costs on the system, however, in most of the contemporary infrastructure's devices usually have limited‐resource. Therefore, second, the lightweight design of access control protocols is also a significant challenge. To address these challenges, we introduce a provably secure and lightweight access control protocol for SGs that eliminates key exchange issues while increasing privacy and security. We evaluate the proposed protocol to determine its security strength against well‐known security attacks. Finally, we present a performance evaluation of the proposed protocol to demonstrate its efficiency in terms of computation and communication costs. Abstract : We proposed an IBC lightweight authentication solution for the SG environment. We exploited lightweight cryptographic operations like message digest/hash functions, exclusive OR, and concatenation to develop a cost‐effective solution. Our protocol guarantees to prevent physical and major cyber threats. A comprehensive comparison of diverse security features reveals the evidence that our authentication solution is equipped with aided security characteristics.